Analysis of Hexagonal Photonic Crystal Fiber Using the Golden Ratio - Rahman, Atta; RAbas, Emeroylariffion; Begum, Feroza (International Journal of Engineering and Technology, 2018)
In this research, the proposed hexagonal photonic crystal fibers design is modelled using the principle of golden ratio; fixing the proportion of pitch to diameter of the air holes constant. Finite element method with perfectly matched layer boundary is used for numerical simulation of different properties. It is shown that the proposed design has lower effective area of below 9 Î¼m2, low chromatic dispersion value of below 57 ps/(km.nm) and confinement loss of less than 0.01 dB/km at 1.55 Î¼m wavelength. The proposed hexagonal photonic crystal fiber is applicable for data transmission systems.Â Â